Geophysical Monitoring Shows that Spatial Heterogeneity in Thermohydrological Dynamics Reshapes a Transitional Permafrost System. Issue 6 (15th March 2021) - Uhlemann, S.; Dafflon, B.; Peterson, J.; Ulrich, C.; Shirley, I.; Michail, S.; Hubbard, S. S.
Abstract: Climate change is causing rapid changes of Arctic ecosystems. Yet, data needed to unravel complex subsurface processes are very rare. Using geophysical and in situ sensing, this study closes an observational gap associated with thermohydrological dynamics in discontinuous permafrost systems. It highlights the impact of vegetation and snow thickness distribution on subsurface thermohydrological properties and processes. Large snow accumulation near tall shrubs insulates the ground and allows for rapid and downward heat flow. Thinner snow pack above graminoid results in surficial freezing and prevents water from infiltrating into the subsurface. Analyzing short‐term disturbances, we found that lateral flow could be a driving factor in talik formation. Interannual measurements show that deep permafrost temperatures increased by about 0.2°C over 2 years. The results, which suggest that snow‐vegetation‐subsurface processes are tightly coupled, will be useful for improving predictions of Arctic feedback to climate change, including how subsurface thermohydrology influences CO2 and CH4 fluxes. Plain Language Summary: When permafrost thaws, water can flow quicker through the ground, creating a very complex subsurface flow system. In this study, we gain detailed insight into these complex processes by measuring the electrical resistivity of the ground daily. Our results show that the type of vegetation and the snow pack that accumulates on it in winter control the temperatures of the ground, and therefore also how water flows. Above tall shrubs snow accumulates much more than above grass. Therefore, temperatures below shrubs are warmer and water and energy from snowmelt and rain can flow through the ground quickly, while colder temperatures below the grass prevent this rapid flow. Longer term dynamics show us that the temperature of permafrost at about 10 m depth increased by 0.2°C over a period of 2 years. The results of this study should be useful for improving predictions of Arctic feedback to climate change. Key Points: Transitional permafrost systems evolve through complex infiltration pathways and energy fluxes, including lateral flow Snow pack and vegetation distribution play major role in permafrost thermohydrological responses Monitoring shows spatially variable thermohydrological responses and intra to inter‐annual dynamics in discontinuous permafrost systems